Implementasi Marketing MIX Dalam Upaya Peningkatan Penjual Butik Muslimah Di Kota Tanjung Pura - Isnaida Isnaida; Muhizar Muchtar; Muhammad Arfan Harahap (Yayasan Rahmat Islamiyah, 2022)
The purpose of this research is to find out how the implementation of marketing mix in an effort to increase sales at Muslimah Tanjung Pura boutiques. The type of research used in this research is the qualitative type using descriptive analysis methods. Data collection is done through observation, structured interviews or interviews, and documentation. The results of this study show that the Muslimah Boutique